математика

Приведите данное уравнение к виду ax^2+bx+c=0 1.) (x+3)^2+(x-2)^2=x^2-5x 2.) (2x-3)(x+5)-2=11-(x-4)^2 3.) (5x-1)(5x+1)+20x^2=7x-3 4.) (8-x)(8+x)+(1-4x)^2=12x^2+1  Подскажите как это решается  x^2 это x во 2-степени

Оставить ответ
1

Ответ №1

1) (x+3)^2+(x-2)^2=x^2-5x \\ x^2+6x+9+x^2-4x+4=x^2-5x   \\ 2x^2+2x+13-x^2+5x=0 \\ x^2+7x+13=0 \\  \\ 2)(2x-3)(x+5)-2=11-(x-4)^2 \\ 2x^2+10x-3x-15-2=11-x^2+8x-16 \\ 2x^2+7x-17-11+x^2-8x+16=0 \\ 3x^2-x-12=0 \\  \\ 3)(5x-1)(5x+1)+20x^2=7x-3 \\ 25x^2-1+20x^2=7x-3 \\ 45x^2-1-7x+3=0 \\ 45x^2-7x+2=0 \\  \\ 4)(8-x)(8+x)+(1-4x)^2=12x^2+1  \\ 64- x^{2} +1-8x+16x^2=12 x^{2} +1 \\ 15x^2-8x+65-12 x^{2} -1=0 \\ 3 x^{2} -8x+64=0

Знаете ответ?